The influence of thermal processing on emulsion properties of defatted hazelnut flour - Turan, Deniz; Altay, Filiz; Çapanoğlu Güven, Esra (Elsevier BV, 2015)
In this study, the influences of roasting and the amount of hazelnut flour on the formation and stabilization of emulsions containing different amounts of oil were investigated. After hazelnuts were roasted in an oven at 140°C for 40 min, the oil content was removed. The emulsions with defatted hazelnut flour containing corn oil at 3%, 10% and 50% were prepared. Roasting process significantly decreased the interfacial tension values of samples down to 1.9 mN/m due to protein denaturation. There was no significant difference between the particle sizes of oil droplets in emulsions with roasted and raw hazelnut flour at the same concentration. However, diffusion coefficients of oil droplets increased for emulsions containing roasted defatted flour samples. The zeta (ζ) potential values of all emulsions increased when roasted hazelnut flour was used, indicating the stabilization of suspensions and the solution resistance against aggregation. Storage modulus (G'), loss modulus (G″) and complex viscosity (η(∗)) of emulsions were measured. G' value was found to be greater than the G″ value, which fits into weak gel model. The roasting process resulted with lower transition temperatures but with increased transition enthalpies of the flour samples based on differential scanning (DSC) measurements. Lower transition temperatures may be attributed to the partial gelatinization of starch in the flour and partial denaturation of proteins. These results may help to tailor the properties of defatted hazelnut flour when it is used in food products containing emulsions such as sauces, dressings and creams for stabilizing purposes.
Keywords: Corylus; Flour; Thermodynamics; Emulsions; Particle Size